Effects of Flue Gas Addition on the Premixed Oxy-methane Flames in Atmospheric Condition. (August 2015) - Li, Yueh-Heng; Chen, Guan-Bang; Chao, Yei-Chin
Abstract: This numerical study investigates the flame characteristics of premixed methane with various inert gas dilutions in order to simulate oxy-combustion of hydrocarbon fuels with flue gas recirculation system. In general, a flue gas consists of high concentration CO2 /H2 O and high gas temperature. The diluent gas in oxy-combustion has been changed compared with air-combustion, so that the flame behavior and combustion characteristics of oxy-fuel must be influenced. By observing the resultant flame temperature and species concentration profiles can identify that the flame location shifts, and the concentration profile of major chemical reaction radicals varies, indicating the change of flame structure and flame chemical reaction paths. The dominant initial consumption reaction step of methane shifts from R53 (H+CH4 =CH3 +H2 ) to R98 (OH+CH4 =CH3 +H2 O) when nitrogen is replaced by the recirculated gases. It is because that the chemical effects of the recirculated gases changes the flame reaction pathway, and further affect reaction rate, species and radical concentrations.